Fasilitasi Pembentukan Asosiasi Bank Sampah (ASBAK) Di Kecamatan Dukun Kabupaten Gresik Problematika Dan Potensi Sampah - Robbah Khunaifih; Abdul Ghofur; Duta Bintan Fitriyah; Mar’atus Sholihah; Shohifatul Wahyuni; Nailis Sa’adah (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Garbage seems to be a useless and useless item. However, if waste understands how to manage it, it can have a high value from an economic point of view. The Gresik Regency Garbage Bank Association (Asbak) is an institution that initiates the movement of waste management from what was originally useless to something useful and has economic value. In its movement to care for the environment, Ashbak Gresik collaborates with the Gresik Regency Environmental Service in order to socialize the existence of the Waste Bank as a special community forum for waste management from and back to the community for its use. No exception in the Dukun Subdistrict, Gresik Regency, this Waste Bank was formed. The method of community service carried out by the STEI Kanjeng Sepuh PkM Team in collaboration with several mass organizations, both from the Indonesian Women's Coalition (KPI) Kec. Dukun and BKMM (Coordination Board for Mosque Taklim Council)-DMI Kec. The shaman was carried out in an open and democratic manner, which eventually led to the selection of a qualified environmental cadre in their field as the Director of the Waste Bank to lead several environmental cadres in the context of caring for waste. After the presentation by the Environment Service and Activists from Ashtray, in this activity, a demonstration of the manufacture of eco-enzyme fertilizer was carried out. Eco enzyme is the result of the fermentation of organic kitchen waste such as fruit and vegetable pulp, sugar (brown sugar, brown sugar or cane sugar), and water. It is dark brown in color and has a strong sweet and sour fermented aroma. Eco Enzyme can be a multipurpose liquid and its applications include households, agriculture and livestock. Basically, eco enzyme accelerates bio-chemical reactions in nature to produce useful enzymes using fruit or vegetable waste